DAMPAK KUALITAS INSTRUKTUR PELATIHAN TERHADAP EFEKTIVITAS PELATIHAN : BERDASARKAN STUDI PENELITIAN PADA PELATIHAN E-LEARNING INSTRUKTUR DAERAH SENSUS PERTANIAN 2023 DI BPS PROVINSI BANTEN - Badarani, Purwanto (Jurnal Bina Bangsa Ekonomika, 2025)
Online training has great potential to be effective in the era of technological and information development, especially if it is implemented well and adapted to the needs of participants. A combination of advanced technology, good curriculum design, and adequate support can overcome many existing shortcomings. This research is to examine how the quality of training instructors impacts training effectiveness. Apart from that, we want to see the influence of other variables on the effectiveness of the training, such as the quality of training materials and training methods. The objects of this research were 105 people who were trained as Regional Instructors in the ST2023 field data collection activities at BPS Banten Province. Empirical data testing uses Structural Equation Modeling (SEM). The research results show that instructor quality positively and significantly affects training effectiveness. The research results recommend increasing the ability or competency of training instructors